Clinical Research on the Mechanisms Underlying Immune Checkpoints and Tumor Metastasis - Tang, Xi-Yang; Shi, An-Ping; Xiong, Yan-Lu; Zheng, Kai-Fu; Liu, Yu-Jian; Shi, Xian-Gui; Jiang, Tao; Zhao, Jin-Bo (Frontiers in Oncology, 2021)
This study highlights aspects of the latest clinical research conducted on the relationship between immune checkpoints and tumor metastasis. The overview of each immune checkpoint is divided into the following three sections: 1) structure and expression; 2) immune mechanism related to tumor metastasis; and 3) clinical research related to tumor metastasis. This review expands on the immunological mechanisms of 17 immune checkpoints, including TIM-3, CD47, and OX-40L, that mediate tumor metastasis; evidence shows that most of these immune checkpoints are expressed on the surface of T cells, which mainly exert immunomodulatory effects. Additionally, we have summarized the roles of these immune checkpoints in the diagnosis and treatment of metastatic tumors, as these checkpoints are considered common predictors of metastasis in various cancers such as prostate cancer, non-Hodgkin lymphoma, and melanoma. Moreover, certain immune checkpoints can be used in synergy with PD-1 and CTLA-4, along with the implementation of combination therapies such as LIGHT-VTR and anti-PD-1 antibodies. Presently, most monoclonal antibodies generated against immune checkpoints are under investigation as part of ongoing preclinical or clinical trials conducted to evaluate their efficacy and safety to establish a better combination treatment strategy; however, no significant progress has been made regarding monoclonal antibody targeting of CD28, VISTA, or VTCN1. The application of immune checkpoint inhibitors in early stage tumors to prevent tumor metastasis warrants further evidence; the immune-related adverse events should be considered before combination therapy. This review aims to elucidate the mechanisms of immune checkpoint and the clinical progress on their use in metastatic tumors reported over the last 5 years, which may provide insights into the development of novel therapeutic strategies that will assist with the utilization of various immune checkpoint inhibitors.